Application of Fuzzy Logic to Predict Rice Production Quantity in Bogor Regency - Dhia Suhaila; Muhammad Hafizh Maulidan; Muchammad Alifandhino Satrio; Ananditto Daffa Wijayanto; Muhammad Danang Mukti Darmawan; Fiqri Nurfadillah; Nanda Octavia (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
This study aims to understand prediction methods using fuzzy Mamdani logic to conclude the quantity of rice production in the Bogor Regency area. Then in this study, we used quantitative methods and involved interviews with resource persons, namely rice mill workers and farmers. The data obtained from the interview is then fuzzyfication to be used in calculations. The main finding of this study is the elaboration of crop quantity from small, normal, and many, with the range of yields produced ranging from 0 to 3000 KG for little, 3000 to 6000 KG for normal, and 6000 to 10000 KG for many. Weather and humidity observations were found to significantly affect rice yields. The implications of these findings are improved accuracy in yield estimation, and the ability to address uncertainty and complexity in factors affecting crop growth. Despite the limitations of this study, such as limited data and remote study locations, the use of fuzzy logic can make a crucial contribution to determining the quantity of water needed for plant growth based on rainfall and weather conditions. This research is crucial because it can be a reference for future research that uses fuzzy logic to determine the quantity of rice production.